Communication Experiences of Exemplary Agricultural Extension Workers with Non-Agricultural Education in Tangerang Regency - Pamungkas, Anjas Satria; Roem, Elva Ronaning; Azwar, Azwar (Mahesa Research Center, 2024)
The activities of agricultural extension involve a communication process between the extension agent and the farmers. An extension agent with deep agricultural knowledge and good communication skills can establish effective communication with farmers. In Tangerang Regency, there is an extension agent named Ratna who, despite having a non-agricultural and non-communication educational background, won the exemplary extension agent award at the Tangerang Regency level in 2021. This study aims to understand the communication experiences of agricultural extension from the perspective of an exemplary agent with a non-agricultural background. This study employs a qualitative method with a constructivist paradigm. The approach used is Edmund Husserl's phenomenology, focusing on understanding the essence of individual experiences, combined with Albert Bandura's social learning theory, emphasizing observation and imitation in the learning process. The results indicate that Ratna's communication experience in extension involves a strong motivation to learn and significant role models in her journey. Motivation drives her to continually improve her skills and knowledge. Moreover, role models provide inspiration and concrete examples of how an extension agent should act and communicate with farmers.